MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MATA PELAJARAN IPS MELALUI PENERAPAN MODEL PEMBELAJARAN MASTERY LEARNING - Alia Uswah (JIEBAR : Journal of Islamic Education: Basic and Applied Research, 2022)
Based on the analysis of daily repeat results or midterm and semester repeats, it is known that the learning outcomes of students in MTs.N 3 Rembang Class VIII for the 2019/2020 school year in IPS subjects are low.  This is shown by the following facts: Learners who get grades below KKM there are 50%, students who get the same value as KKM there are 35% and students who get a score above KKM there is 15%. It is expected that from the learning carried out is the learning outcome of learners in IPS subjects at least 30% of learners achieve grades above KKM, 50% of learners achieve the same value as KKM, and 20% of learners achieve grades below KKM. This research includes a type of classroom action research (PTK), with its main characteristic being repeated actions and the main method is self-reflection aimed at improving learning. PTK is a problem-solving activity characterized by cyclic and reflection that starts from: a) planning, b) actions, c) observing, d) analyzing data/information to decide the extent of the advantages and disadvantages of such actions (reflecting). PTK is characterized by continuous improvement so that research satisfaction is often the benchmark of the cycle. From the analysis of the causes of the problem, the efforts that are expected to improve the learning outcomes of Class VIII learners in IPS subjects are the application of the right model, namely a learning model that allows students to conduct exercises, discussions, direct guidance of teachers until learners can solve IPS subject problems. The model that is suspected to be right is the Mastery Learning model. The steps of this model are (1) Orientation, (2) Presentation, (3) Structured exercises, (4) Guided exercises, (5) and Self-Training. This class action research is to find out the increase in the activeness and learning outcomes of class VIII MTs Negeri 3 Rembang odd students in 2019/2020 in the IPS through the application of the Mastery Learning model.